2010
DOI: 10.3354/meps08805
|View full text |Cite
|
Sign up to set email alerts
|

Survival and life strategy of the foraminiferan Globobulimina turgida through nitrate storage and denitrification

Abstract: In a laboratory experiment, we examined the prolonged survival and behaviour of the benthic foraminiferan Globobulimina turgida under 3 simulated natural conditions: oxygenated with added nitrate, anoxic with added nitrate, and anoxic. The survival rates, adenosine triphosphate (ATP) reserve and intracellular nitrate pool of G. turgida were measured periodically under these conditions. Furthermore, to evaluate the efficiency and energy yield of the respiration system, denitrification rates of individual specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 44 publications
5
65
0
Order By: Relevance
“…Being able to perform respiration by denitrification in the absence of oxygen was first observed for two benthic species by RisgaardPetersen et al (2006). This surprising ability to accumulate nitrate and its respiration to dinitrogen gas was later confirmed in benthic foraminifera in OMZ sediments off the Chilean coast (Hogslund et al, 2008) and demonstrated in laboratory experiments (Pina-Ochoa et al, 2010). However, in at least one species, symbiotic bacteria appear to be responsible for respiring the nitrate, not the foraminifera (Bernhard et al, 2012).…”
mentioning
confidence: 80%
“…Being able to perform respiration by denitrification in the absence of oxygen was first observed for two benthic species by RisgaardPetersen et al (2006). This surprising ability to accumulate nitrate and its respiration to dinitrogen gas was later confirmed in benthic foraminifera in OMZ sediments off the Chilean coast (Hogslund et al, 2008) and demonstrated in laboratory experiments (Pina-Ochoa et al, 2010). However, in at least one species, symbiotic bacteria appear to be responsible for respiring the nitrate, not the foraminifera (Bernhard et al, 2012).…”
mentioning
confidence: 80%
“…Small changes in near-saturated oxygen conditions are not expected to impact survivorship of aerobic foraminifera. Previous studies indicated that Globobulimina can live in a low-oxygen environment and is able to survive short periods of anoxia (Corliss, 1985(Corliss, , 1991RisgaardPetersen et al, 2006;Piña-Ochoa et al, 2010;Koho et al, 2011). The ability of G. turgida to survive such conditions depends, at least partly, on denitrification, using nitrate stored in an internal pool within its cytoplasm (Piña-Ochoa et al, 2010;Koho et al, 2011).…”
Section: Survivorshipmentioning
confidence: 99%
“…Sediments from the 125-500-µm size fraction were picked for G. turgida. Individual specimens of G. turgida that had green/brown coloration, indicating algal uptake (Piña-Ochoa et al, 2010;Koho et al, 2011), were deemed alive and introduced to the experimental setup. In total ~650 individuals were selected, and divided among the 6 treatments in this experiment (Table 2; ~100-110 specimens per treatment).…”
Section: Sedimentmentioning
confidence: 99%
See 2 more Smart Citations